Autonomic nervous system modulation and clinical outcome after pulmonary vein isolation using the second‐generation cryoballoon. (21st June 2017) - Miyazaki, Shinsuke; Nakamura, Hiroaki; Taniguchi, Hiroshi; Hachiya, Hitoshi; Kajiyama, Takatsugu; Watanabe, Tomonori; Igarashi, Miyako; Ichijo, Sadamitsu; Hirao, Kenzo; Iesaka, Yoshito
Abstract: Background: The intrinsic cardiac autonomic nervous system (ANS) plays a significant role in atrial fibrillation (AF) mechanisms. This study evaluated the incidence and impact of intraprocedural vagal reactions and ANS modulation by pulmonary vein isolation (PVI) using second‐generation cryoballoons on outcomes. Methods: One hundred three paroxysmal AF patients underwent PVI with one 28‐mm second‐generation balloon. The median follow‐up was 15.0 (12.0–18.0) months. ANS modulation was defined as a >20% cycle length decrease on 3‐minute resting electrocardiograms at 1, 3, 6, and 12 months postindex procedure relative to baseline if sinus rhythm was maintained. Results: Marked sinus arrests/bradycardia and atrioventricular block (intraprocedural vagal reaction) occurred in 14 and 2 patients, and all sinus arrest/bradycardia occurred in 44 patients with left superior pulmonary veins (PVs) targeted before right PVs. ANS modulation was identified in 66 of 95 (69.5%) patients, and it persisted 12‐month postprocedure in 36 (37.9%) patients. Additional β‐blocker administration was required in 9 patients for sinus tachycardia. ANS modulation was similarly observed in patients with and without intraprocedural vagal reactions (P = 0.443). Forty‐eight (46.6%) patients experienced early recurrences, and the single procedure success at 12 months was 72.7%. Neither intraprocedural vagal reactions nor ANS modulation predicted AF freedom within or after the blanking period. Thirty‐three patients underwent second procedures, and reconnections were detected in 39 of 130 (30.0%) PVs among 23 (69.7%) patients. The incidence of reconnections was similar in patients with and without ANS modulation. Conclusions: Increased heart rate persisted in 37.9% of patients even at 12‐month post‐second‐generation cryoballoon PVI. Neither intraprocedural vagal reactions nor increased heart rate predicted a single procedure clinical outcome.